Causes of visual impairment: a retrospective study in Macedonian children - Dimitrova Radojichikj, Daniela; Tasevska, D. (Journal of Ophthalmology (Ukraine), 2020)
Background: Reliable data on the prevalence and causes of visual impairment in children are necessary for developing a systematic vision screening program with valid and reliable test protocols. Purpose: The aim of the study was to investigate the prevalence, main causes, and associated factors of visual impairment among Macedonian children aged 0–18 years. Methods: This retrospective study analyzed the clinical record of 829 children, attending the department of ophthalmology from October 2013 to October 2018. The following variables were investigated: age, gender, and diagnosis. Results: The prevalence of visual impairment was statistical significance higher in girls than in boys (p<0.05), with a male to female ratio of 1/1.2 .The most frequent diagnostics were refractive errors (42.6%), ocular inflammation (20.6%), and strabismus (9%). Conclusion: In our country, data on the prevalence, magnitude and causes of visual impairment in children are needed for planning and evaluating preventive and curative services for children, and for planning special education and low vision services.
Keywords: visual impairment, causes, prevalence